2005
DOI: 10.1002/jmv.20516
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of hepatitis B virus ‘a’ determinant variants in unselected Spanish chronic carriers

Abstract: The prevalence in the population of hepatitis B virus (HBV) surface antigen (HBsAg) variants that may impair diagnosis, or allow the virus to escape vaccine‐induced immunity or passive immunoglobulin therapy is unknown. A genome fragment encoding HBsAg amino acids 112–212 was amplified and sequenced from the sera of 272 unselected DNA‐positive, HBV‐chronic carriers from Spain. The genotype and the HBsAg subtype were predicted from the sequences. Analysis of amino‐acid positions 112–157 revealed single or multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
125
7
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 40 publications
(55 reference statements)
10
125
7
7
Order By: Relevance
“…Several previous studies identified typical HBsAg amino acid substitutions are sP120T, sM133I, sS143L, sD144A/E, sG145R, sE164D, sW172*, and sW182* which is the most commonly occurring pattern (9,15,16). Vaccine escape/HBIg-selected escape mutants, sG145R and sP120T, in combination with LAM-associated resistance mutations, are often seen in HBV mono-infected patients after LAM or HBIg treatment (31).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several previous studies identified typical HBsAg amino acid substitutions are sP120T, sM133I, sS143L, sD144A/E, sG145R, sE164D, sW172*, and sW182* which is the most commonly occurring pattern (9,15,16). Vaccine escape/HBIg-selected escape mutants, sG145R and sP120T, in combination with LAM-associated resistance mutations, are often seen in HBV mono-infected patients after LAM or HBIg treatment (31).…”
Section: Discussionmentioning
confidence: 97%
“…The present study is also the first of its kind to report typical HBsAg amino acid substitutions in Turkish HD patients infected with CHB. Some of the detected mutations (sP120T, sG130R, sM133L/T, sY134N, sD144E, sS143L, and sG145R) have been shown to cause diagnostic problems in HBsAg assays and vaccine or HBIg therapy escape (16). However, insufficient data is available for interpretation, and the clinical effects of some of the detected typical HBsAg amino acid substitutions found in this study (i.e., sY100C/S, sL109R, sI110L, sS117G/N, sP127T, and sS132C/P) are not clear in the background literature (16).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some of the previously developed HBsAg measurement kits could not detect HBsAg when such mutations were present; the kits using MAbs were found to be especially prone to being unable to detect mutants (17,28). Our present method utilizing the BLEIA attempted to solve this problem by combining multiple MAbs with a rabbit polyclonal antibody.…”
Section: Discussionmentioning
confidence: 98%
“…The HBV genome exhibits a high rate of mutations due to its reverse transcription process (12,13), leading to the generation of a wide variety of mutations (14,15) that may alter viral protein conformation and antigenicity. These mutations include those within the major hydrophilic region (MHR) of the S protein, including the T/I126S, T123N, C124R, Q129H, D144A, and G145R mutations (3,(16)(17)(18)(19)(20). It is known that some of the existing diagnostic reagents used for the detection of HBsAg cannot detect such HBsAg mutants even when a sufficient antigen concentration is present in the blood samples.…”
mentioning
confidence: 99%
“…Dado que la vacunación de la población susceptible es fundamental para el control de la infección por el VHB, la comunidad científica se afana por diseñar nuevos prototipos de vacunas que disipen este problema. En este sentido, incorporar a la vacuna clásica HBsAg recombinantes con las mutaciones más frecuentes o utilizar como antígeno un HBsAg recombinante en el que el primer loop del domino hidrofílico, aminoácidos 121-129 del determinante "a", o la región PreS resulten inmunodominantes, son opciones cuya factibilidad debe ser elucidada en un futuro próximo 60 . La aparición de virus con las mutaciones anteriormente citadas es un hecho conocido desde hace tiempo; sin embargo, ni la prevalencia en población general ni en portadores crónicos ha sido establecida, por lo que el comportamiento epidemiológico de estas mutantes no se conoce en realidad.…”
Section: Importancia Epidemiológica De Las Mutantes De Escapeunclassified